Education on the Use of Maggots to Foster Environmental Awareness Among Residents of Kedaung Village - Ardhana, Andesta Wahyu; Utomo, Pandu Setyo; Wahyu, Nurvita Dewi; Elvira, Nurul Wira; Salsabila, Noor Laeli; Yusti, Mistika; Tokan, Imelda; Cahyani, Fanny Gita; Julika, Delta; Wahyudin, Siti Nur Azizah (Academia Publication, 2025)
This community service project aims to enhance the environmental awareness of Kedaung residents by promoting maggot utilization as an eco-friendly organic waste decomposer. The main issue addressed is the large amount of household organic waste that remains poorly managed. The project employed the Asset-Based Community Development (ABCD) and Participatory Action Research (PAR) methods, which included stages of socialization, educational material delivery, hands-on practice, and participatory evaluation. The results revealed an improvement in the participants’ understanding and skills in small-scale maggot cultivation, as well as the emergence of local initiatives to separate organic waste and develop maggot-based microenterprises. The activity not only contributed to a cleaner and healthier environment but also created economic opportunities through maggot sales and compost utilization. Therefore, maggot utilization education proved effective in fostering environmental awareness and empowering the community toward ecological and economic sustainability.